2009
DOI: 10.1016/j.ccr.2009.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Metastasis after Short-Term Treatment with a Potent Inhibitor of Tumor Angiogenesis

Abstract: SUMMARY Herein we report that the VEGFR/PDGFR kinase inhibitor sunitinib/SU11248 can accelerate metastatic tumor growth and decrease overall survival in mice receiving short-term therapy in various metastasis assays, including after intravenous injection of tumor cells or after removal of primary orthotopically grown tumors. Acceleration of metastasis was also observed in mice receiving sunitinib prior to intravenous implantation of tumor cells, suggesting possible “metastatic conditioning” in multiple organs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
1,265
12
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,582 publications
(1,360 citation statements)
references
References 29 publications
69
1,265
12
14
Order By: Relevance
“…In addition to the importance of Arf6 in tumour angiogenesis, it has been reported that Arf6 activation in cancer cells is required for cancer invasion and metastasis 50 . Recent preclinical studies have suggested that anti-angiogenic therapy may promote cancer invasion and metastasis by inducing hypoxia of cancer cells, suggesting that effective cancer therapeutic approaches should involve both inhibition of tumour angiogenesis and cancer invasion/metastasis 51,52 . The critical roles of Arf6 in both tumour vascularization and cancer cell invasiveness/metastasis provide a new cancer therapeutic opportunity.…”
Section: Nature Communications | Doi: 101038/ncomms8925mentioning
confidence: 99%
“…In addition to the importance of Arf6 in tumour angiogenesis, it has been reported that Arf6 activation in cancer cells is required for cancer invasion and metastasis 50 . Recent preclinical studies have suggested that anti-angiogenic therapy may promote cancer invasion and metastasis by inducing hypoxia of cancer cells, suggesting that effective cancer therapeutic approaches should involve both inhibition of tumour angiogenesis and cancer invasion/metastasis 51,52 . The critical roles of Arf6 in both tumour vascularization and cancer cell invasiveness/metastasis provide a new cancer therapeutic opportunity.…”
Section: Nature Communications | Doi: 101038/ncomms8925mentioning
confidence: 99%
“…However, although antitumoural effects and survival benefit are often evident, relapse to progressive tumour growth has been recently reported, reflecting multiple mechanisms of adaptation to anti-angiogenic therapies. 25,26 In this context, D133p53 may have a critical role by stimulating angiogenesis through pathways involving several angiogenic factors distinct from VEGF. Thus, targeting D133p53 may have a strong impact in cancer therapeutics.…”
Section: D133p53a Stimulates Angiogenesis H Bernard Et Almentioning
confidence: 99%
“…These treatments effectively inhibit tumor progression through deprivation of oxygen and nutrition from the tumor microenvironment, but cannot block metastasis of RCC cells. Moreover, there is growing evidence that antiangiogenic therapies can accelerate invasion and metastasis by making the tumor microenvironment more fertile (4,5).…”
Section: Introductionmentioning
confidence: 99%